Borca katılma - Altay, Sabah (My University, 2010)
TEZ ÖZETİ Borca katılma, bir kişinin borçlunun edimini alacaklıya karşı üstlenerek, müteselsil borçlu olması şeklinde tarif edilen bir sözleşmedir. Bu sözleşme teminat vermek amacıyla yapılır. Borçlulardan birini edimi yerine getirmesiyle borç sona erer. Teminat vermek amacı, kefalet sözleşmesiyle benzerlik meydana getirir. Kefalet sözleşmesine ilişkin bazı hükümlerin kıyasen bu sözleşmeye uygulanması mümkündür. Borçlar kanununun 141-147 hükmü borca katılmaya uygulanır. THESIS

Cumulative assumption of debt is a type of contract which is described as, undertaking debtor's obligation and being solidary obligator with the first debtor. This contract is usually performed for the aim of giving guarantee for the debtors obligation to the creditor. The aim of giving guarantee for the obligation makes this contract's character smiliar to the contract of cautionement and that is why legal analogie is possible between the rules of the both contracts. The rules 141-147 of code of obligations are applied to the contract of cumulative asumption of debt.
Keywords: Borçlar; Hukuk; Özel Hukuk